HPLC Method to Standardize Secondary Metabolites of Plant Extract: Application to Ziziphus nummularia and Eclipta prostrata: RP-HPLC method to standardize Z. nummularia and E. Prostrata extract. - Kamboj, Anjoo; Kumar, Sachin; Malhotra, Hitesh (Iranian Journal of Pharmaceutical Sciences, 2024)
Investigating intricate plant extracts poses a formidable task in unearthing new bioactive compounds with therapeutic potential. Thus, the need for a rapid and sensitive method is crucial to ensure the quality and efficacy of herbal products in the botanical industry. A robust RP-HPLC technique was created, validated, and employed to separate, detect, and measure phytoconstituents. This method was then utilized for the analysis of chloroform extracts from the leaves of Eclipta prostrata and hydroethanolic extracts from Ziziphus nummularia. The RP-HPLC method involved employing a mobile/solvent phase of acetonitrile: methanol (7:3 v/v) at a constant flow rate of 1 mL/min, and the analysis was conducted at a wavelength of 208 nm. Eluted peaks were detected at retention times of 2.11±0.023 min, 3.233±0.045 min, 3.437±0.126 min, and 4.120±0.137 min, corresponding to rutin, stigmasterol, β-sitosterol, and quercetin, respectively. The response exhibited linearity in the range of 0.2-0.8 μg/ml, with a regression coefficient exceeding 0.991. The limits of detection (LOD) and quantification (LOQ) for these components ranged from 0.692-1.92 ng/ml and 2.10-10.45 ng/ml, respectively. This developed method demonstrated precision, specificity, reproducibility, and accuracy. It was subsequently applied to assess the content of dried leaf powder from E. prostrata and Z. nummularia. The RP-HPLC method has the potential to be beneficial for assessing both the qualitative and quantitative aspects of the components found in plant extracts and herbal products.